2020
DOI: 10.1038/s41467-020-16376-5
|View full text |Cite
|
Sign up to set email alerts
|

Animal biosynthesis of complex polyketides in a photosynthetic partnership

Abstract: Complex polyketides are typically associated with microbial metabolism. Here, we report that animals also make complex, microbe-like polyketides. We show there is a widespread branch of fatty acid synthase-(FAS)-like polyketide synthase (PKS) proteins, which sacoglossan animals use to synthesize complex products. The purified sacogolassan protein EcPKS1 uses only methylmalonyl-CoA as a substrate, otherwise unknown in animal lipid metabolism. Sacoglossans are sea slugs, some of which eat algae, digesting the ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 61 publications
(86 reference statements)
3
78
0
Order By: Relevance
“…This finding indicates that the carbon donor (malonyl-CoA) during this elongation process was 13 C-enriched and thereby preferentially provided by kleptoplasts. Torres et al [25] reported that methylmalonyl-CoA incorporating kleptoplast fixed-carbon is used by sacoglossan sea slugs in the synthesis of UV-and oxidation-blocking polypropionate pyrones by the action of FA synthase-like proteins. Pyrones could be critical for maintaining long-term photosynthetic activity in sacoglossan sea slugs by serving antioxidant and photoprotective roles [17,25].…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the carbon donor (malonyl-CoA) during this elongation process was 13 C-enriched and thereby preferentially provided by kleptoplasts. Torres et al [25] reported that methylmalonyl-CoA incorporating kleptoplast fixed-carbon is used by sacoglossan sea slugs in the synthesis of UV-and oxidation-blocking polypropionate pyrones by the action of FA synthase-like proteins. Pyrones could be critical for maintaining long-term photosynthetic activity in sacoglossan sea slugs by serving antioxidant and photoprotective roles [17,25].…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis of secondary metabolites by animal biochemistry is a barely explored, blooming field [93]. In those cases, in contrast to finding pathways from symbiotic bacteria, the tool required is transcriptomics, so that genes expressed by the animal are analyzed and subsequently their products are biochemically characterized [94].…”
Section: Discussion: the Chemistry And Chemical Potential Of Didemnummentioning
confidence: 99%
“…Polypropionates with different carbon skeleton were also described from genus Siphonaria (Gastropoda: Tectipleura) such as Siphonaria baconi Reeve, 1856 (now accepted as Siphonaria zelandica Quoy and Gaimard, 1833) 43 , and Siphonaria diemenensis Quoy and Gaimard, 1833 44 . Moreover, other marine molluscs, like photosynthetic members of the order Sacoglossa, harbor a big complex of different polypropionates acting as photoprotectants and antioxidants within the slugs 45,46 . These compounds seem to be common within the Onchidiidae and are reported from various localities, including China, Hawaii, and Australia 18,44,47 .…”
Section: Discussionmentioning
confidence: 99%